Застосування проектно-орієнтованого підходу в управлінні інноваційною діяльністю - Пітерська, Варвара Михайлівна (НТУ "ХПІ", 2016)
У статті розглянуті питання державної підтримки наукових досліджень в Україні та запропонований методичний підхід щодо розробки проектно-орієнтованої стратегії інноваційного розвитку наукової діяльності, враховуючи світовий досвід забезпечення виконання досліджень згідно сучасних програм розвитку науково-технічного сектору. Використання проектно-орієнтованого управління інноваційною діяльністю пояснюється необхідністю скоротити цикл досліджень і підсилити контроль за витрачанням коштів у зв'язку з обмеженням фінансування науково-дослідних робіт з боку держави.

The article describes the current state of science in Ukraine, indicated the main directions of research funding. The methodological approach of working out of the project-oriented strategy of innovative development of scientific activity, including the implementation of international trends and support of research is proposed. Using of project-oriented approach of research activities due to the need of reducing of the research cycle and strengthen expenditure control capabilities due to restrictions of funding research projects from the state. It should be noted that the structuring of research, given the project approach, allows engaging of the implementation of the research project professionals with good knowledge and skills and create a team activity focused on quality results. Innovations aren‘t still properly means the improvement of competitiveness in Ukraine. Thus the problem of transition to an innovative development model retains its relevance, that significantly enhanced in the light of current external and internal trends. Using of the project-oriented innovation management due to the need to shorten the cycle of research and to strengthen the control over the expenditure of funds in connection with the limited funding of scientific research by the state.
Using of the project-oriented approach in the innovative activity management
Keywords: управління проектами; розвиток науково-технічний; модернізація; технології; фінансування; project management; scientific activities; innovative development